Tinjauan Intermestik dalam Mekanisme Kebijakan Perubahan Iklim Global (REDD-UNFCCC): Persfektif Indonesia - Apriwan, Apriwan (Jurnal Hubungan Internasional, 2014)
The international regime of the United Nations Framework Convention on Climate Change (UNFCCC) has resulted some agreements and policies which binding its countries member. The latest one was the mechanism of REDD (Reducing Emissions From Deforestation and Forest Degradation). The implemetantion of these mechanism does not only bind and involve the countries member at the national level but also at local level (such as at province and regency level). Local aspect has a significant role as the basis for implementing these policy. This paper examines how instermestic perspective used for explaining the relation between international and domestic (local) aspect within the REDD-UNFCCC mechanism.